O brincar e o bem-estar da criança abrigada: sua influência no combate à depressão e ao baixo rendimento escolar - Zogaib, Maria Teresa Bertoncini (2006)
This study examines the effectiveness of play intervention among institutionalized children with learning problems and depression symptoms, analyzing the influence of play in their well being and quality of life. The study was carried out using as methodology clinical intervention among eight children of both gender, aged eight, low income group, living in support homes for 2 years, first grade of elementary public school, with school complaint. After the characterization of the institution, individually assesses children s cognitive level using Raven s Progressive Colored Matrices, Piagetian tests of conservation, classification and series and verifies the school material. Following applies the Children s Depression Inventory CDI, standardized to Brazil. Based on this information, carry out eight weekly ninety-minute group play session using sensory-motor, symbolic and social strategies with room for spontaneous activity. After the play intervention, re-assesses the children using the same instruments from previous evaluation. The results show better school performance and decrease of depressive symptoms, with increase of self-steam and emotional confidence, reflecting in their life in general, including at school. The experiences lived during the play situations contributed for a better subjective self-evaluation from children, as well as a better school evaluation in their integrated cognitive and affective-emotional aspects. The results point out the importance of early recognition of depressive symptoms by technical team to start intervention programs, using the play to facilitate institutionalized children to overcome cognitive and affective difficulties